A comparative study of students’ performance in flipped classroom and structured interactive session teaching learning method in Conservative Dentistry and Endodontics - Sushmita Shrestha; Mannu Vikram; Navin Agrawal; Ashok Ayer; Ashish Shrestha (Journal of Gandaki Medical College, 2023)
Introduction: Flipped classroom is an element of blended learning, integrating both face-to-face learning in the class through group discussion and distance learning outside the class by watching video lessons and online collaboration. The objective of the study was to introduce and assess the effectiveness of flipped classroom in teaching and learning of Conservative Dentistry and Endodontics and to understand the perspective of students about the same.